Exploring Intercultural Dynamics in Medical English Education in China: an In-depth Analysis and Strategic Enhancement - Zhou , Guojun; Mohammed, Lubna Ali (Journal of Ecohumanism, 2024)
With the continuous development of modern society, information transmission has become more rapid and convenient, which has gradually increased the economic exchanges among various countries in the world, and has also led to more frequent communication among political, cultural, medical and other fields between different regions. At the same time, the mutual penetration and integration between foreign medical culture spread through English and domestic traditional medical concepts have also put forward new demands for the cultivation of high-quality talents in China’s medical field. Researchers have explored the cross-cultural complexity of Medical English Teaching (MET) in Chinese higher education institutions and its impact on global medical communication. With the increasing internationalization of healthcare services, English, as the main language of medical communication, is gaining prominence in education. In this broader context. The status of English in global medical education and its teaching in non-native English-speaking environments are facing great challenges, especially in China’s higher education settings. Based on an in-depth analysis of the literature and empirical research, this study reveals cross-cultural barriers to MET practice and adopts a mixed-methods research design that combines both quantitative and qualitative methods of data collection and analysis in order to comprehensively examine the current status of MET in China. Special attention was paid to teachers’ intercultural competence development, teaching method innovation, and course content adaptation. Based on this, the researcher proposes targeted strategies aimed at improving intercultural competence in MET, including strengthening teacher training, improving curriculum design, and promoting the integration of intercultural communication skills. The findings of the study not only provide insights into existing MET practices, but also offer constructive suggestions for future educational strategies and research directions. Through this study, we expect to contribute a valuable reference and guidance to the field of medical English education in China and globally.